Pandemic 2009 Influenza A (H1N1) Infection in Children - Taner Özgür; Enes Salı; Mustafa Turhan Hacımustafaoğlu; Solmaz Çelebi; Deniz Çakır (Güncel Pediatri)
Introduction: The aim of this study is to share our experience of sixty-eight pediatric hospitalizations associated with influenza-like illness and pneumonia between November, 2009 and December, 2009.Materials and Methods: Clinical signs and symptoms, laboratory and radiological results, length of stay in hospital and intensive care unit, treatments and complications were compared in laboratory confirmed pandemic influenza A positive and negative cases.Results: There was no significant difference in gender distribution between the two groups. The number of positive cases in patients over 5 years of age were significantly higher than the same age group in negative patients (p=0.004). There were underlying health conditions in 78.8% of the positive cases and in 68.8% of the negative cases (p=0.57). The incidence of diarrhea in positive group was significantly higher than in the negative group (p=0.02). Low immunization rates of the seasonal influenza vaccine were remarkable in each group. There was no significant difference in vaccination rates between the two groups (p=0.99).Conclusions: The severity of the disease remained similar in patients with positive and negative groups. In both groups, the high ratio of those having an underlying disease was noteworthy. (Journal of Current Pediatrics 2011; 9: 53-9)Key words: Pandemic 2009 influenza A, childhood, pneumonia